Evaluation of Physiological and biochemical traits of selected soybean line in Makurdi - Okoh, J. O.; Achiv, R. Y; Shaahu, A (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
Twelve genotypes of soybean were selected for physiological and seed biochemical evaluations at Joseph Sarwuan Tarka University, Makurdi. These seeds were collected from NCRI Badegi; Niger State- Nigeria. Ten of these genotypes S1075-6-93, S1179-6-58, S1239-6-135, S1240-6-288, S1252-6-277, S1252-6-156, S1268-6-15, S1273-6-65, S1365-6L-20 and SC SENTINEL is newly introduced to Makurdi while SC SIGNA and SLO1 used as checks have been released. The seed crop field was laid out in a Randomized Complete Block Design (RCBD) with three replications in 4-rows of 5m long. Seed samples were collected and subjected to seed quality tests at the Department of Plant Breeding and Seed Science Laboratory of the University. Data were collected on germination count which was expressed as germination percentage and its (germination rate and germination rate index) were consequentially obtained. These seeds were also subjected to proximate analysis and percentage protein, fat, ash, moisture content and crude fibre were determined using soxhlet method. The result showed that significant differences existed for germination rate index (GRI) and germination index (GI) while other seedling traits were not different in magnitude from each other. Protein was highest in three varieties (S1075-6-93, S1239-6-135 and S1252-6-156) with 40.25%, respectively and significantly different from others and the checks. SC SENTINEL had the least protein content (37.19) and highest oil content (20.82). Meanwhile, genotype S1239-6-135 had the least oil content (18.83). Compositionally, an inverse relationship existed between protein oil in genotypes studied. Biochemical composition has more effect on seed quality of these soybean genotypes than physiological traits. Genotypes (S1075-6-93, S1239-6-135 and S1252-6-156) had higher protein content than the checks. Also, Sc SENTINEL, S1365-6L-20, S1273-6-65, S1268-6-15 and S1240-6-288 had higher oil content than the checks. Soybean oil producers could use SC SENTINEL for their productions and (S1075-6-93, S1239-6-135 and S1252-6-156) could be used for protein-based products.